Sensory integration and activities of daily living in children with developmental coordination disorder - Elbasan Bülent; Kayıhan Hlya; Duzgun Irem (BMC, 2012)
Abstract Objective The aim of our study was to evaluate sensory integration and activities of daily living in children with developmental coordination disorder Subjects and methods 37 cases with developmental coordination disorder and 35 healthy age-matched peers were included in this study. Ayres Southern California Sensory Integration Test was used for evaluating the sensory integration and Functional Independence Measure for Children (WeeFIM) was used for evaluating the activities of daily living. Results Significant differences were found in the visual shape perception, position in space, and design copying (p < 0.05). According to the results of somatosensory perception tests, significant differences were found in kinesthesia, manual form perception, finger identification, figure-ground perception, localization of tactile stimuli, double tactile stimuli perception (p < 0.05). Control group was better in motor planning (p < 0.05). Comprehension, expression, social communication, problem solving, and memory skills were significant in favor of the control group (p < 0.05). Graphestesia and self-care domain was found to be correlated (r = 0,491, p = 0.002) between the groups. Discussion Special education and rehabilitation programs including sensory integration therapy and motor performance will increase independence in the activities of daily living in children with developmental coordination disorder.